Organismus und Technik Anthologie zu einem produktiven und problematischen Wechselverhältnis - Liggieri, Kevin; Tamborini, Marco (Wissenschaftliche Buchgesellschaft (wbg), 2021)
Through the technologies of the 20./21. century the living organism became a "tool". Organic-physical demarcations are undermined, so that organism and technology no longer oppose each other, but merge with each other. The anthology presents different philosophical approaches to this problem relationship.